2008
DOI: 10.1103/physrevc.78.044305
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between eigenvalues and diagonal matrix elements

Abstract: We investigate eigenvalues of many-body systems interacting by two-body forces as well as those of random matrices. We find a strong linear correlation between eigenvalues and diagonal matrix elements if both of them are sorted from the smaller values to larger ones. By using this linear correlation we are able to predict reasonably all eigenvalues of given shell model Hamiltonian without complicated iterations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Indeed the correlation is remarkably good. We found that this correlation is well applicable not only to realistic systems, but also to any two-body random ensemble [3]. Below we give a few examples.…”
Section: Linear Correlation Between Eigenvalues and Diagonal Matrix Ementioning
confidence: 82%
See 1 more Smart Citation
“…Indeed the correlation is remarkably good. We found that this correlation is well applicable not only to realistic systems, but also to any two-body random ensemble [3]. Below we give a few examples.…”
Section: Linear Correlation Between Eigenvalues and Diagonal Matrix Ementioning
confidence: 82%
“…An example is shown on the left side of Fig. 1, which shows the distribution of eigenvalues E First we sort the matrix elements H (I) i j in such a way that the diagonal elements are sorted from smaller values to larger ones [3]:…”
Section: Linear Correlation Between Eigenvalues and Diagonal Matrix Ementioning
confidence: 99%
“…Mr. Shen started this practice when he was an undergraduate student in Shanghai. He made two interesting progresses in his undergraduate thesis [14]: (1) he considered the third moment and improved our statistical formula. (2) He accidentally noticed an interesting correlation between eigenvalues and diagonal matrix elements for a shell model Hamiltonian, after sorting the diagonal matrix elements from the smaller to the larger.…”
Section: Two Recent Resultsmentioning
confidence: 99%
“…[10,11], we sorted diagonal matrix elements from the smaller to larger ones, and found a very strong (statistical) linear correlation between exact eigenvalues E i and diagonal matrix elements H…”
Section: A Regular Pattern Of the Distribution Of The Matrix Elementsmentioning
confidence: 98%
“…Along the same line, Yoshinaga et al [6,7] studied the lowest energy of spin I states by the moments of energy spectra based on the fact that the eigenvalues of Hamiltonian under two-body random ensemble follow the Gaussian distribution [8,9] . Recently, we found linear (statistical) correlation between eigenvalues and diagonal matrix elements in the nuclear shell model Hamiltonian [10,11] .…”
mentioning
confidence: 98%